549 Injury prevention and safety promotion. It is not that simple. (20th November 2022) - Hanson, Dale
Abstract : In Australasia, our indigenous Aboriginal and Mouri forbears bring a rich understanding about how place impacts on our existence and the language and knowledge we use to explain it. Does our place in the injury prevention, safety promotion or policy communities determine our interpretation of human exitance and the language and knowledge we use to describe it? Analysis: In 1999, Dave Snowden, proposed the Cynefin Framework to aid decision making about social phenomenon. 'Cynefin' is Welsh for habitat (place). Snowdon suggests there are five different decision making contexts (habitats) that require fundamentally different approaches. Simple problems (known, knowns) are addressed by applying well established knowledge (Best Practice). Complicated problems (known unknowns) Good practice requires synthesis of different types of expertise (academic, research, practitioner, administrators and the target community) Complex problems (unknown unknowns). Optimum practice is found by identifying 'emerging patterns' of system behaviour, that is necessarily more experimental, in a real-world context. Problems and their solutions are incrementally revised or refined based on outcome. Chaotic problems (unknowable). The objective is to get the situation sufficiently under control that they can again be analysed and addressed. Disordered (wicked) problems. No one can agree on what the problem is, much less how to solve it. Solving these problems is not about who is 'right' or 'wrong' but building sufficient consensus to meaningfully intervene. Learning Outcomes: Injury prevention and community safety promotion reside in different ontological and epistemological habitats that necessarily require different approaches to research, decision making, implementation and promulgation of optimum practice.